Meningkatkan Motivasi Belajar Siswa SD Melalui Bimbingan Belajar Di Dusun Gombong Kabupaten Magelang - Nailatul Muna; Arvina Istiqomah (Khidmatan, 2021)
Online learning provides a new experience for students who usuallyenjoy face-to-face lessons. This makes students have more free time, which is generally only actualized into less valuable activities such as playing gadgets too often. This service aims to optimize students' free time and help students understand the material that was previously difficult to understand. The method used in this study is ABCD (Asset-Based Community Development). The assistance provided in tutoring activities is expected to help students understand the material obtained from the school. This service concludes that students enjoy the learning process at the tutoring place, but students cannot focus properly because they like to play with friends and mentors.